RANCANG BANGUN WEB E-COMMERCE SEBAGAI SARANA MARKET DIGITAL KELOMPOK USAHA SEUKE TEULAYA DESA MATANG GLEUM KABUPATEN ACEH TIMUR - Saumi, Fazrina; Rahmawati, Rahmawati; Salman, Salman; Almi, Rahmad (Universitas Muhammadiyah Tapanuli Selatan, 2021)
The Seuke Teulaya group is one of the groups engaged in the processing of pandanus leaves to become more valuable. The problems faced by partners so far are (a) Limited markets in distributing production products from the Seuke Teulaya business group, (b) Marketing is still carried out conventionally, namely through traditional markets, hawkers, and agents (c) Sales results in general have not been able to cover costs production. The PKM team offers a solution, namely by expanding the marketing coverage area and the information technology approach in the form of digital sales by building the Seuke Teulaya business group's e-commerce web and third-party e-commerce webs such as Bukalapak, Tokopedia, and Shoope as well as promotion on social media (Facebook, Instagram , and WhatsApp). The output of this program is national online media publications, local print media, activity videos, non-accredited journals, e-commerce websites that are integrated with Instagram, Facebook, and WhatsApp as well as seller accounts on Bukalapak, Tokopedia, and Shoope.